Pattern and Frequency of Seroreactivity to Routinely Used Serologic Tests in Early-Treated Infants With HIV. (1st March 2020) - Puthanakit, Thanyawee; Ananworanich, Jintanat; Akapirat, Siriwat; Pattanachaiwit, Supanit; Ubolyam, Sasiwimol; Assawadarachai, Vatcharain; Sawangsinth, Panadda; Jupimai, Thidarat; Anugulruengkitt, Suvaporn; Tawan, Monta; Kosalaraksa, Pope; Borkird, Thitiporn; et al.
Abstract : Background: Previous studies have shown low frequencies of seroreactivity to HIV diagnostic assays for infected infants treated with antiretroviral therapy (ART) early in infection. Methods: Fifty-eight HIV-infected infants treated with ART at a median age of 1.9 months (range: 0.2–5.4) for up to 4 years of life were assessed for seroreactivity to 4 routinely used HIV clinical immunoassays (IA): Second-generation (2ndG) IA and 2 rapid diagnostic tests (RDT), based on third-generation principles, measuring antibody only and a fourth-generation (4thG) antigen/antibody IA. HIV Western blot assay was also performed to assess HIV-specific antibodies. Results: The 2ndG IA demonstrated the highest frequency of seroreactivity in children (69%) followed by the 4thG IA (40%) and the RDT (26%) after one year of ART. Infants initiating ART during ages 3–6 months (N = 15) showed a greater frequency (range: 53%–93%) and breadth (median and range: 3 [1–4]) of reactivity across the assays compared with those treated within 3 months (N = 43):16%–61% and breadth (1 [0–4]). The 4thG IA showed significantly reduced reactivity relative to the 2ndG IA at one ( P = 0.016) and 3 ( P = 0.004) years of ART. Western blot profiles following 3 years of ART showed the highest frequency of reactivity to HIV Gag p24 (76%) and lowest reactivity to Env gp120 and gp41, with only 24% of children confirmed positive by the assay. Conclusions: These results suggest that the use of 4thG IA and RDT test combination algorithms with limited HIV antigen breadth may not be adequate for diagnosis of HIV-infected children following early treatment. Abstract : Supplemental Digital Content is Available in the Text.